2020
DOI: 10.1159/000513588
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profiles and the Effect of Intravitreal Aflibercept Treatment on Experimental Choroidal Neovascularization

Abstract: Purpose: The purpose of our study was to investigate the profiles of inflammatory cytokines and the macrophage polarization gene in a choroidal neovascularization (CNV) mouse model before and after intravitreal aflibercept treatment. Methods: The CNV mouse model was conducted by laser photocoagulation. A total of 58 cytokines were measured by multiplex mouse cytokine antibody array. The macrophage polarization genes were tested by reverse transcription polymerase chain reaction. The relationship between the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…MIP-1a was signi cantly correlated with the CNV lesion area, suggesting that the migration of MIP-1a-mediated macrophages could induce an in ammatory response and affect CNV formation. [22] Our novel results showed elevated aqueous humor concentrations of MIP-1α and MIP-1β in eyes with neovascular AMD. We believe that these ndings are attributed to a disrupted RPE cell regulation because of degeneration and suggest that in ammatory factors may in uence the pathogenesis of AMD.…”
Section: Discussionmentioning
confidence: 58%
“…MIP-1a was signi cantly correlated with the CNV lesion area, suggesting that the migration of MIP-1a-mediated macrophages could induce an in ammatory response and affect CNV formation. [22] Our novel results showed elevated aqueous humor concentrations of MIP-1α and MIP-1β in eyes with neovascular AMD. We believe that these ndings are attributed to a disrupted RPE cell regulation because of degeneration and suggest that in ammatory factors may in uence the pathogenesis of AMD.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, it was confirmed that MIP-1a was significantly increased in a study targeting the laser-induced CNV mouse model. MIP-1a was significantly correlated with the CNV lesion area, suggesting that the migration of MIP-1a-mediated macrophages could induce an inflammatory response and affect CNV formatio n [26]. Our novel results showed elevated aqueous humor concentrations of MIP-1α and MIP-1β in eyes with wet AMD.…”
Section: Fig 2 Correlation Between the Volume Of Subretinal Fluid (Sr...mentioning
confidence: 56%
“…These marker genes represent different M2 macrophage subpopulations, suggesting that different macrophage subtypes have distinct roles at different time-points during the pathological process of CNV. Specifically, M2a macrophages may be associated with neovascularisation, whereas M2b and M2c macrophages may be involved in fibrous scarring ( 195 ).…”
Section: Intraocular Neovascularisation-related Diseasesmentioning
confidence: 99%